What happens when we modify mosquitoes for disease prevention? - Nazareth, Teresa (2020)
The release of modified mosquitoes to suppress/replace vectors constitutes a promising tool for vector control and disease prevention. Evidence regarding these innovative modification techniques is scarce and disperse. This work conducted a systematic review, gathering and analysing research articles from PubMed and Biblioteca Virtual em Saúde databases whose results report efficacy and non-target effects of using modified insects for disease prevention, until 2016. More than 1500 publications were screened and 349 were analysed. Only 12/3.4% articles reported field-based evidence and 41/11.7% covered modification strategies’ post-release efficacy. Variability in the effective results (90/25.7%) questioned its reproducibility in different settings. We also found publications reporting reversal outcomes 38/10.9%, (e.g. post-release increase of vector population). Ecological effects were also reported, such as horizontal transfer events (54/15.5%), and worsening pathogenesis induced by natural wolbachia (10/2.9%). Present work revealed promising outcomes of modifying strategies. However, it also revealed a need for field-based evidence mainly regarding epidemiologic and long-term impact. It pointed out some eventual irreversible and important effects that must not be ignored when considering open-field releases, and that may constitute constraints to generate the missing field evidence. Present work constitutes a baseline of knowledge, offering also a methodological approach that may facilitate future updates.